HUBUNGAN KEKUATAN OTOT DAN FLEKSIBILITAS SENDI DENGAN PRESTASI RENANG 50 M GAYA KUPU-KUPU - Setyawan, Tri Tunggal (Universitas Negeri Semarang, 2007)
The research has been conducted to find out the correlation between the powerof muscles and the flexibility of joints during a 50 m distance butterfly stoke. Thefindings could be used to rise athletes’ achievement. The subject of research consistedof 10 males athletes, aging from 14 up to 24 years. The variables were the power ofvarious limb muscles when doing butterfly stroke for 50 m distance. To measure thosethe research used the leg dynamitor, the pull and push dynometer, the anthropometer,the flexometer, and the stopwatch. The single and multiple regression analyses havebeen indicated that there were negative correlation between (a) the various musclesduring a 50 m butterfly stroke and (b) the power of muscles and the flexibility ofjoints. It proved too that male athletes have certain muscles that strongly influencethem. Those are the pulling and pushing power of muscles, the flexibility of shoulderjoints, and the plantar flexi joints.Kata Kunci: kekuatan otot, fleksibilitas sendi, renang gaya kupu-kupu